LabVIEW Based Fast Tracking MPPT Algorithm for PV Systems Using Voltage Sensor. (2020) - Mathew, Johnson; Shanifa Beevi, S.; Vincent, G.
Abstract: This paper proposes a fast-tracking MPPT algorithm for PV systems, where the operating voltage of the module is driven directly to the voltage at the maximum power point. Unlike heuristic MPPT methods which are executed with perturbation and correction approach, this proposal estimates the MPP which is the destination of the operating point, at the very first iteration itself. This maximum power is not directly computed but the voltage corresponding to the maximum power point is estimated and continuously refreshed using the mathematical model of the module corresponding to the changing climatic conditions. Thus it totally eliminates the possibility of drift in its tracking. Another important feature of this algorithm is that it is able to efficiently work even under partially shaded conditions of the module by driving the operating point to the global maxima of the P-V curve. The efficacy of the proposal is validated through extensive experimental studies with real-time data acquisition.